2022
DOI: 10.1371/journal.pone.0275072
|View full text |Cite
|
Sign up to set email alerts
|

Hcmv-miR-UL148D regulates the staurosporine-induced apoptosis by targeting the Endoplasmic Reticulum to Nucleus signaling 1(ERN1)

Abstract: The propensity of viruses to co-opt host cellular machinery by reprogramming the host’s RNA-interference machinery has been a major focus of research, however, regulation of host defense mechanisms by virus-encoded miRNA, is an additional regulatory realm gaining momentum in the arena of host-viral interactions. The Human Cytomegalovirus (HCMV) miRNAs, regulate many cellular pathways alone or in concordance with HCMV proteins, thereby paving a conducive environment for successful infection in the human host. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
(104 reference statements)
0
0
0
Order By: Relevance
“…Among the potential targets identified, we consider ERN1, ATF4, BID and FAS worthy of further attention. Regarding ERN1, research indicates that ERN1 mRNA is the actual target of hcmv-miR-UL148D and its encoded protein IRE1α is translationally repressed by the overexpression of hcmv-miR-UL148D resulting in the attenuation of apoptosis [ 72 ]. Regarding ATF4, research has demonstrated that activated transcription factor 4 (ATF4) plays a pivotal role as the key transcription factor in ERS [ 73 ], and is at least partially implicated in ERS-mediated apoptosis [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the potential targets identified, we consider ERN1, ATF4, BID and FAS worthy of further attention. Regarding ERN1, research indicates that ERN1 mRNA is the actual target of hcmv-miR-UL148D and its encoded protein IRE1α is translationally repressed by the overexpression of hcmv-miR-UL148D resulting in the attenuation of apoptosis [ 72 ]. Regarding ATF4, research has demonstrated that activated transcription factor 4 (ATF4) plays a pivotal role as the key transcription factor in ERS [ 73 ], and is at least partially implicated in ERS-mediated apoptosis [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…When canonically binding to the 3′UTR, they typically destabilize the transcript and trigger the degradation pathway of cellular mRNAs [69]. v-miRs have also been shown to bind to the 5′UTR, preventing translation without altering mRNA levels in the cell [70,71]. Alternatively, v-miRs binding to the 5′UTR can increase mRNA stability, preventing degradation and upregulating gene expression [14,72].…”
Section: Pro-viral Mirna Regulation Of Viral Infectionmentioning
confidence: 99%
“…The use of miRNA gives viruses the ability to control gene expression and manipulate host cell activities to their benefit. miRNAs have been implicated in many processes during infection, including viral entry, viral replication, latency and reactivation, immune evasion, immune suppression or overactivation, inflammation, host cell survival, tumorigenesis, and more [10,13,14,43,[69][70][71]77,[80][81][82][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. See Tables 1 and 2 for recent research developments in miRNA regulation of viral infection.…”
Section: Pro-viral Mirna Regulation Of Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation